Probing cellulose–solvent interactions with self-diffusion NMR: Onium hydroxide concentration and co-solvent effects. (1st March 2023) - Medronho, B.; Pereira, A.; Duarte, H.; Gentile, L.; Rosa da Costa, A.M.; Romano, A.; Olsson, U.
Abstract: The molecular self-diffusion coefficients were accessed, for the first time, in solutions of microcrystalline cellulose, dissolved in 30 wt% and 55 wt% aqueous tetrabutylammonium hydroxide, TBAH (aq), and in mixtures of 40 wt% TBAH (aq) with an organic co-solvent, dimethylsulfoxide (DMSO), through pulsed field gradient stimulated echo NMR measurements. A two-state model was applied to estimate α ( i.e., average number of ions that "bind" to each anhydroglucose unit) and Pb ( i.e., fraction of "bound" molecules of DMSO, TBAH or H2 O to cellulose) parameters. The α values suggest that TBA + ions can bind to cellulose within 0.5 TBA + to 2.3 TBA + /AGU. On the other hand, the Pb parameter increases when raising cellulose concentration for TBA +, DMSO and water in all solvent systems. Data suggests that TBAH interacts with the ionized OH groups from cellulose forming a sheath of bulky TBA + counterions which consequently leads to steric hindrance between cellulose chains. Graphical abstract: Unlabelled Image